Pengembangan Desa Wisata Budaya Puncak Wangun Pasirmulya Kabupaten Bandung Melalui Perancangan Brand Identity dan Media Promosi Digital - Nanang Ganda Prawira; Arief Johari; Aditya Aditama Putri Hikmatyar; Fika Tria Widaningsih (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
The collaboration between the Forest Village Community Institution (LMDH) and the Department of Culture and Tourism (Disbudpar) on the National Community Empowerment program succeeded in turning the Puncak Wangun Cultural Tourism Village into an alternative tourist destination for the people of Bandung and its surroundings. This tourist village has a lot of potential from interesting artistic, cultural, socio-economic and ecological aspects, but the existence of Puncak Wangun Cultural Tourism Village is not widely known to the public. To introduce the potential of tourist villages, improve marketing communications, and provide visual branding, a visual identity design was carried out through Community Service activities by applying the Design Thinking method and SWOT analysis guided by field activities, interviews, and Focus Group Discussions. This PKM program succeeded in designing a brand identity that was applied to digital promotional media for the Puncak Wangun Cultural Tourism Village in the form of a website and Instagram. In the future, it is necessary to develop a brand identity that is applied to souvenir products, sign systems, packaging, or other products according to the needs and interests of partners to expand the popularity of Puncak Wangun Cultural Tourism Village in attracting tourists from various demographic segments in order to advance tourist destinations and communities.